Tumor Necrosis Factor Alpha-Induced Recruitment of Inflammatory Mononuclear Cells Leads to Inflammation and Altered Brain Development in Murine Cytomegalovirus-Infected Newborn Mice - Seleme, Maria C. (J Virol, 2017)
Congenital human cytomegalovirus (HCMV) infection is a significant cause of abnormal neurodevelopment and long-term neurological sequelae in infants and children. Resident cell populations of the developing brain have been suggested to be more susceptible to virus-induced cytopathology, a pathway thought to contribute to the clinical outcomes following intrauterine HCMV infection. However, recent findings in a newborn mouse model of the infection in the developing brain have indicated that elevated levels of proinflammatory mediators leading to mononuclear cell activation and recruitment could underlie the abnormal neurodevelopment. In this study, we demonstrate that treatment with tumor necrosis factor alpha (TNF-α)-neutralizing antibodies decreased the frequency of CD45(+) Ly6C(hi) CD11b(+) CCR2(+) activated myeloid mononuclear cells (MMCs) and the levels of proinflammatory cytokines in the blood and the brains of murine CMV-infected mice. This treatment also normalized neurodevelopment in infected mice without significantly impacting the level of virus replication. These results indicate that TNF-α is a major component of the inflammatory response associated with altered neurodevelopment that follows murine CMV infection of the developing brain and that a subset of peripheral blood myeloid mononuclear cells represent a key effector cell population in this model of virus-induced inflammatory disease of the developing brain. IMPORTANCE Congenital human cytomegalovirus (HCMV) infection is the most common viral infection of the developing human fetus and can result in neurodevelopmental sequelae. Mechanisms of disease leading to neurodevelopmental deficits in infected infants remain undefined, but postulated pathways include loss of neuronal progenitor cells, damage to the developing vascular system of the brain, and altered cellular positioning. Direct virus-mediated cytopathic effects cannot explain the phenotypes of brain damage in most infected infants. Using a mouse model that recapitulates characteristics of the brain infection described in human infants, we have shown that TNF-α plays a key role in brain inflammation, including recruitment of inflammatory mononuclear cells. Neutralization of TNF-α normalized neurodevelopmental abnormalities in infected mice, providing evidence that virus-induced inflammation is a major component of disease in the developing brain. These results suggest that interventions limiting inflammation associated with the infection could potentially improve the neurologic outcome of infants infected in utero with HCMV.